PH‐Sensing Hydrogel Fibers: Flexible pH‐Sensing Hydrogel Fibers for Epidermal Applications (Adv. Healthcare Mater. 6/2016). Issue 6 (March 2016) - Tamayol, Ali; Akbari, Mohsen; Zilberman, Yael; Comotto, Mattia; Lesha, Emal; Serex, Ludovic; Bagherifard, Sara; Chen, Yu; Fu, Guoqing; Ameri, Shideh Kabiri; Ruan, Weitong; Miller, Eric L.; et al.
Abstract : On page 711 S. Sonkusale, A. Khademhosseini, and co‐workers present pH‐responsive hydrogel fibers that can be used for long‐term monitoring of epidermal wound conditions. pH‐responsive dyes are loaded into mesoporous microparticles, which are then embedded into hydrogel fibers developed through microfluidic spinning. The fabricated pH‐responsive microfibers are flexible and can create conformal contact with skin. Images of the pH‐sensing fibers during real‐time pH measurement can be captured with a smart phone camera for convenient readout on‐site.